Alcohol use disorder in patients with emergency application - Şengül, Cem; Serinken, Mustafa; Balcı Şengül, Ceyhan; Yüksel, Aykut; Aydın, Berrin (Journal of Dependence, 2010)
Objective: Alcohol using disorders was one of the most concerning problems for emergency department staff. Valid and reliable screening tests were needed for better diagnosis of alcohol related problems. In this study we aimed to investigate the emergency application of people with alcohol using disorders.Methods: We screened the alcohol using disorders with CAGE and AUDIT questionnaires. Data were evaluated with SPSS 11.0 software.Results: Total of 574 patients was evaluated with CAGE and AUDIT questionnaires. 39
Keywords: Alcohol; emergency department; screening; CAGE; AUDIT